1986
DOI: 10.1159/000298884
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by Somatostatin of LH-RH-Induced LH Release in Normal Menstruating Women

Abstract: The present study was carried out in order to establish whether the concomitant treatment with somatostatin (SRIH) is capable of modifying gonadotrophin release in response to LH-RH administration in normal women during follicular, periovulatory, and luteal phases. SRIH was administered in a dose of 5.55 µg/min over 180 min and LH-RH (100 µg) was injected as a bolus at 90 min after the beginning of SRIH infusion. Within the dose used, SRIH significantly reduced LH response to LH-RH, whereas it did not alter FS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 5 publications
1
9
1
1
Order By: Relevance
“…Although somatostatin analogues might affect LH secretion in premenopausal patients (Chiodera et al, 1986), in our postmenopausal patients no significant effects on plasma E2 levels were observed. This finding confirms the results of the study of Manni et al (1989) who also found no effect of combined octreotide/bromocriptine treatment on plasma LH, FSH and E2 levels.…”
Section: Anti-tumour Effectscontrasting
confidence: 69%
“…Although somatostatin analogues might affect LH secretion in premenopausal patients (Chiodera et al, 1986), in our postmenopausal patients no significant effects on plasma E2 levels were observed. This finding confirms the results of the study of Manni et al (1989) who also found no effect of combined octreotide/bromocriptine treatment on plasma LH, FSH and E2 levels.…”
Section: Anti-tumour Effectscontrasting
confidence: 69%
“…Somatostatin is a 14-amino acid endogenous hypothalamic peptide with a short half-life that, besides blunting the LH response to gonadotropin-releasing hormone (GnRH) (110) and decreasing growth hormone (GH) pituitary secretion (111), inhibits pancreatic insulin release (112). Somatostatin analogs should therefore be potential drugs for the treatment of PCOS.…”
Section: New Potential Drug: Somatostatin Analogsmentioning
confidence: 99%
“…In our study, PCOS women had much lower SS levels than the control, a significantly negative correlation be tween basal LH and SS existed in group 1. It was found that SS could induce a significant decrease in LH ampli tude by directly or indirectly lowering the sensitivity of gonadotrophs to gonadotropin-releasing hormone [2], An SS analogue, octreotide, was reported to suppress LH and ovarian androgen secretion in PCOS and to result in a more 'appropriate' hormonal milieu [6], These observa tions support that insufficient endogenous SS may be responsible for elevated LH levels in PCOS women, espe cially of group 1. Furthermore, a reduced Ei level not only causes a reduced negative feedback on LH release by the pituitary, but also results in an impaired opioid-mediated inhibitory control on GnRH by the hypothalamus [7], Increased gonadotropin secretion by opioid antagonism was expected in normal women but not found in PCOS women.…”
Section: Discussionmentioning
confidence: 99%